Personality, Social Support and Workers' Stress - Dolan, Shimon; van Ameringen, Marie; Arsenault, André (Relations industrielles / Industrial Relations, 1992)
The study examines social support as a correlate of perceived job demands and psychological strain and as a moderator of the relationship between stimulus and response, according to personality traits. 807 hospital employees were administered an occupational stress questionnaire. Data was obtained regarding two sources of job demands (intrinsic and extrinsic), three psychological symptoms (anxiety, depression and irritation), four categories of personality and three areas of social support. Using hierarchical regression procedures (Arnold 1982) the results suggest that the effects of social support vary significantly depending upon the source of job demands, the workers' personality and the psychological symptom manifested.